Controllable selenium vacancy engineering in basal planes of mechanically exfoliated WSe2 monolayer nanosheets for efficient electrocatalytic hydrogen evolution. Issue 99 (23rd November 2016) - Sun, Ying; Zhang, Xuewei; Mao, Baoguang; Cao, Minhua
Abstract : Se-vacancy-rich WSe2 monolayer nanosheets with excellent electrocatalytic hydrogen evolution activity were prepared by mechanical exfoliation and annealing of bulk WSe2 . Abstract : Engineering intrinsic selenium vacancies (Se-vacancies) was achieved in mechanically exfoliated WSe2 monolayer nanosheets (WSe2 MLNSs) via an annealing treatment. Our theoretical and experimental results reveal that these Se-vacancies can efficiently activate and optimize the basal planes of the WSe2 MLNSs. As expected, the optimized catalyst exhibits efficient electrocatalytic hydrogen evolution.